The Role of the EU in Shaping Kosovo’s Political Future: A Critical Analysis - Burim Mexhuani (Cogent Social Sciences)
This paper critically analyzes the role of the European Union (EU) in shaping Kosovo’s political future, with a particular focus on the successes, challenges, and implications of the EU’s involvement for Kosovo-Serbia relations. Drawing on existing literature and primary sources, the paper compares the EU’s approach to Kosovo with its policies towards other countries in the region, including Bosnia and Herzegovina and North Macedonia. Through this comparative analysis, the paper highlights the unique challenges that Kosovo faces in its efforts to integrate with the EU, including the lack of recognition from five EU member states and ongoing political disputes with Serbia. Additionally, the paper examines the impact of EU conditionality on Kosovo’s domestic politics, particularly in relation to corruption and the rule of law. Overall, the paper argues that while the EU has played a significant role in shaping Kosovo’s political future, ongoing challenges and uncertainties may impact Kosovo’s path towards EU accession.